Compendium of African sub-regional human rights documents - Solomon Ebobrah (Pretoria University Law Press (PULP), 2010)
About the publication African sub-regional inter-governmental organisations are taking on an increasingly important role in the promotion and protection of human rights. It is against the background that knowledge of available standards and mechanisms is crucial for greater enjoyment of the increasing opportunities for remedies for human rights violations that this collection of human rights instruments became necessary. This Compendium brings together relevant instruments from eight sub-regional organisations: the Arab Maghreb Union (AMU), the Common Market for Eastern and Southern Africa (COMESA), the East African Community (EAC), the International Conference on the Great Lakes Region, the Economic Community of Central African States (ECCAS), the Economic Community of West African States (ECOWAS), the Intergovernmental Authority on Development (IGAD) and the Southern African Development Community (SADC). The Compendium also includes a selection of human rights cases decided by the East African Court of Justice, the ECOWAS Court of Justice and the SADC Tribunal. African sub-regional inter-governmental organisations function within the ambit of the African Union (AU). Human rights documents of the AU and resolutions and case law of the African Commission on Human and Peoples' Rights are published in the Compendium of key human rights documents of the African Union also available from PULP. About the editors: Solomon Ebobrah is Extra-ordinary lecturer, Centre for Human Rights and Lecturer, Niger Delta University, Nigeria